Modelling the persuasive visual design model for web design: a confirmatory factor analysis with PLS-SEM - Ibrahim, Nurulhuda; Shiratuddin, Mohd Fairuz; Kok, Wai Wong (IP Publishing LLC, 2018)
Visual design plays an important role in grabbing web users’ attention in an online environment. Previous research has demonstrated that different types of visual design causes different impact towards the end-users. This paper observes the impact of persuasive visual towards users’ first impression, attitudes, and behaviours. It extends existing web visual design by empirically examining the critical roles of the principles of social influence in the form of visual persuasion in motivating users to have a favourable impression of a particular website. Survey data was collected in an experimental study that was conducted online. Structural model assessment is carried out using confirmatory factor analysis (CFA) in conjunction with PLS-SEM analyses. The general analysis of model fit indicates that the two models proposed in this paper surpassed the cut off values for model acceptance with most of the model fit criteria reflects outstanding explanatory power. The result of the analysis indicates that visual persuasion has a big impact in influencing users’ attitudes on the web; strong enough to affect their behavioural intention.